Review of Sand Production Control and Management (Texas Journal of Engineering and Technology, 2022)
Production of the sand becomes a significant problem throughout the life of wells, especially in poorly consolidated reservoirs. This issue frequently leads to tube buckling and abrasion of the down-hole and surface equipment as a result of the inflow of sand. In addition, the costs associated with the loss of hydrocarbon production, work-over operations, and the processes related to the repair and re-installation of the electrical submersible pumps (ESP), and the need for disposal of sand in an environmentally acceptable manner. In this article, the difficulties with sand production that arise during drilling and production operations are thoroughly reviewed. The consequences and mechanisms of sand production, the factors influencing sand production capacity (i.e., sand production causes), as well as the remedial options were discussed. Eventually, this article can be utilized as a reference for any issue concerning sand production in oil and gas wells.